METASTATIC MEDULLARY THYROID CARCINOMA DESPITE PROPHYLACTIC TOTAL THYROIDECTOMY IN MULTIPLE ENDOCRINE NEOPLASIA (MEN) 2A - Wai, Shuit Siew; Ismail, Shartiyah; Merican, Nor Shaffinaz Yusoff Azmi; Abdullah, Noor Rafhati Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Medullary thyroid carcinoma (MTC) is a rare neuroendocrine tumour originating from parafollicular cells. Seventy five percent of MTC occur in a sporadic form while 25% are hereditary and associated with Multiple Endocrine Neoplasia (MEN) type 2. As the age of onset of MTC and penetrance of MTC in MEN2 varies by subtype, prophylactic thyroidectomy is recommended for patients with the highest risk of pathogenic variants. We describe a patient with MEN2a with metastatic MTC 10 years following prophylactic thyroidectomy. CASE A 29-year-old female was diagnosed with MEN2a at the age of 15 years. The diagnosis was made through genetic screening after her mother was diagnosed with the same condition with RET proto-oncogene mutation. She underwent prophylactic thyroidectomy at 16 years old. Her tumour markers, calcitonin and carcinoembryonic antigen (CEA) were within the normal ranges. She had no loco-regional recurrence during serial follow-up. However, her tumour markers were noted to increase 10 years after surgery. CEA doubling time was 19 months indicating progressive disease. Markedly elevated serum calcitonin at 783 pg/ml (<7.6) indicated high tumour burden and likely metastases. Neck ultrasonography did not reveal any disease recurrence. Serial CT scan of the abdomen demonstrated multiple liver lesions suspicious of metastases. Ga-68 DOTATATE and F-18 FDG PET-CT scan showed multiple non-somatostatins nor FDG-avid liver lesions. There were FDG-avid cervical lymph nodes suspicious of nodal metastases. Histopathologic analysis of the liver biopsy specimen confirmed metastatic MTC. She is planning for a multi-targeted tyrosine kinase inhibitor as systemic therapy for metastatic disease. CONCLUSION Management of MTC in the context of MEN2a is challenging and advances in molecular diagnosis and risk stratification systems have led to better individualized treatment and follow-up strategies. Prophylactic thyroidectomy as early as 6 months for the highest risk and before 5 years old for other high-risk codon mutations is crucial in reducing the risk of micro-metastases.